Chemical Composition of Foliage of Exotic Seabuckthorn (Hippophae rhamnoides ssp. Mongolica) - Singh, Virendra; Singh, B. (Indian Forester, 2018)
The present study was carried out on the fodder values of Indian form of seabuckthorn (Hippophae rhamnoides ssp. turkestanica) and an exotic seabuckthorn (H. rhamnoides ssp. mongolica) growing at the farm area of Regional Station of Himachal Pradesh Agricultural University, located at Kukumseri (Altitude 2650 m asl) in district Lahaul-Spiti, a cold desert region of Himachal Himalayas. Crude protein content in the leaves of Indian and exotic forms was similar in May month (30.4% and 29.3% respectively) and it declined to a minimum of 22.8% and 22.3%, respectively in October. EE value increased progressively and it was initially higher in local form (3.5%) than the exotic form (2.5%), however it increased more significantly (P<0.05) in the exotic form (9.6%) than the local form (5.6 %) in October month. ADF values were initially similar, in local form, ADF values decreased significantly (P<0.05) from May (16.4%) to October (14.2%), whereas in exotic form, it was maximum in September (17.5%). NDF value was significantly (P<0.05) higher in local form (29.0%) than the exotic form (26.4%) and it declined in subsequent months, whereas in exotic form, it was maximum (28.6%) in September. Ash content in the local form (10.2%) was significantly (P<0.05) higher than the exotic form (7.5%) and increased to maximum in October (11.1 and 9.8 % respectively) in both cases. High contents of CP and EE and moderate contents of other nutrients make both forms of Seabuckthorn a useful fodder for the livestock of cold desert Himalayas. Seabuckthorn leaves should be preserved as quality feed for livestock during winter.